Komunikasi dan Kreativitas: Apakah Dibutuhkan dalam Organisasi? - Thea Geneveva J. Jesajas (Syntax Idea)
The purpose of this study is to evaluate the influence of communication and creativity variables on performance of employees. The research was conducted at PT Bank XYZ located in Jakarta in April 2023. The population in this study amounted to 82 people where the entire population was sampled (census). The data was analyzed by testing validity and reliability using a data processing application, namely the Statistical Package for the Social Science (SPSS) version 22. The multiple linear regression model used in this research is communication and creative variables as independent variables, performance as dependent variables. It was found that there was no influence between communication and performance. Where creativity has an influence on performance, especially on employee creativity where creativity is still owned by employees even though there are still discrepancies in job position placement. This is because creativity is important in business, because it has four (4) benefits, where in Fosters for Growth it means related to the development of a company that is expected to be able to interpret or see a situation or challenge to clearly understand the circumstances faced by the company, encourage creative thinking of employees so that they can plan actions to be carried out so that the company does not stagnate.